If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9b + 4 = 3b + -2 Reorder the terms: 4 + 9b = 3b + -2 Reorder the terms: 4 + 9b = -2 + 3b Solving 4 + 9b = -2 + 3b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-3b' to each side of the equation. 4 + 9b + -3b = -2 + 3b + -3b Combine like terms: 9b + -3b = 6b 4 + 6b = -2 + 3b + -3b Combine like terms: 3b + -3b = 0 4 + 6b = -2 + 0 4 + 6b = -2 Add '-4' to each side of the equation. 4 + -4 + 6b = -2 + -4 Combine like terms: 4 + -4 = 0 0 + 6b = -2 + -4 6b = -2 + -4 Combine like terms: -2 + -4 = -6 6b = -6 Divide each side by '6'. b = -1 Simplifying b = -1
| -6(2x+-5)=16+2x | | 4-(-6)/x2-4 | | 3(2x-3)=-24 | | 24+3x=3 | | 9-x+3x-2-9x=0 | | X/2-8=-14 | | 6log^8x+2=0 | | 6log^8+2=0 | | -22=g+15 | | 4/x=[72/40]2 | | h/5-h/3=7/15 | | 8(5-2v)-8=3v+13 | | -1/3x-1/2=3/5 | | -5+12=16x-2-15x | | 2(4x)=2x | | 4(3x+1)=3x-7x | | 7.7a-5.8a= | | 13y=12(y+8) | | X-(x*0.05)=800 | | 16y=40+8y | | -9(x-9)=7x+17 | | 1+44=-5(8x-9) | | -22=4(v-8)-6v | | 123-v=179 | | s^2=45-4s-s^2 | | .3/.2=18/? | | X/3- | | 6w+3w=27 | | 3x-450=2816 | | V/-3.3=-14.8 | | -5(5n-5)+3n=0 | | -3y-8x=12 |